Nurse Determinants of the Incidence of Nosocomial Infections in Hospitals - Maria Kurni Menga; Hartaty Hartaty (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Nosocomial infections significantly affect the patient's health and can increase morbidity and mortality. The incidence of nosocomial diseases is still widely found, and nurse compliance in preventing and controlling infections is a significant factor in preventing nosocomial infections. The study aims to analyze the determinants of nurses on the incidence of nosocomial diseases. The study used qualitative methods with total sampling techniques. The results of statistical tests were obtained on the variables sex value p = 0.256, age value p = 1.000, nutritional status p = 0.710, and invasive action p = 1.000. It can be concluded that there is no influence of intrinsic factors (age, sex, and nutritional status) on nosocomial infections, and extrinsic factors that significantly affect the occurrence of nosocomial diseases are antibiotics. While what has no effect is the use of invasive measures. This needs serious attention from nurses because prevention of nosocomial infections will be beneficial in reducing the morbidity rate that occurs in hospitals. Prevention of nosocomial diseases in hospitals can be done by minimizing the administration of invasive measures, especially in patients, increasing special attention to patients who receive invasive procedures, and increasing personal hygiene efforts